Association of Indoor and Outdoor Air Pollution With Hand-Grip Strength Among Adults in Six Low- and Middle-Income Countries. (7th February 2019) - Lin, Hualiang; Guo, Yanfei; Ruan, Zengliang; Kowal, Paul; Di, Qian; Zheng, Yang; Xiao, Jianpeng; Hoogendijk, Emiel O; Dent, Elsa; Vaughn, Michael G; Howard, Steven W; Cao, Zheng; et al.
Abstract: Background: Air pollution has been associated with various health outcomes. Its effect on hand-grip strength, a measurement of the construct of muscle strength and health status, remains largely unknown. Methods: We used the survey data from 31, 209 adults ≥ 50 years of age within Wave 1 of the Study on Global AGEing and Adult Health in six low- and middle-income countries. The outdoor concentration of fine particulate matter pollution (PM2.5 ) was estimated using satellite data. Domestic fuel type and ventilation were used as indicators of indoor air pollution. We used multilevel linear regression models to examine the association between indoor and outdoor air pollution and hand-grip strength, as well as the potential effect modifiers. Results: We found inverse associations between both indoor and outdoor air pollution and hand-grip strength. Each 10 μg/m 3 increase in 3 years' averaged concentrations of outdoor PM2.5 corresponded to 0.70 kg (95% CI: −1.26, −0.14) lower hand-grip strength; and compared with electricity/liquid/gas fuel users, those using solid fuels had lower hand-grip strength (β = −1.25, 95% CI: −1.74, −0.75). However, we did not observe a statistically significant association between ventilation and hand-grip strength. We further observed that urban residents and those having a higher education level had a higher association between ambient PM2.5 and hand-grip strength, and men, young participants, smokers, rural participants, and those with lower household income had higher associations between indoor air pollution and hand-grip strength. Conclusion: This study suggests that both indoor and outdoor air pollution might be important risk factors of poorer health and functional status as indicated by hand-grip strength.